French, Ultras and Moderates : Challenges and tensions at the beginning of the Second Absolutist Restoration in Spain (1823/24) - Butrón Prida, Gonzalo (Hispania Nova, 2022)
This paper analyses the challenges and tensions caused by the policy of moderation inspired by France in 1823 as an alternative to the Spanish constitutional regime. French proposals barely convinced a moderate minority, while their royalist allies clung to absolutism and strongly resisted the political concessions, rendering useless in this respect the enormous military and economic effort made by France during the military campaign. From October onwards, once freed from constitutional control, Ferdinand VII confirmed this same intransigent policy, avoiding any concession, however moderate it might be. He also promoted a policy of punishing the vanquished, which he tried to impose despite the pressure exerted by his allies to grant a wide-ranging amnesty.